Gender equality in mass orienteering - case study of the implementation of new rules in “10mila” - Zernis, Emils (2025)
This master's thesis investigates the implementation of gender equality measures in the mass orienteering event "10mila," the largest orienteering relay competition in Sweden. Despite the increasing interest in gender equality in sports, there is limited research focusing on orienteering. This study aims to analyse how the recent changes to the "10mila" rules have impacted different participant groups and how these changes are perceived across the orienteering community. The research employs a quantitative methodology, analysing survey data from 1,029 participants (408 women, 614 men) collected after the 2024 event. The study draws on theories of gender equality in sports and examines how factors such as competition level, geographic location, and demographic characteristics influence attitudes toward organizational change. The theoretical framework considers both practical implementation challenges and broader cultural aspects of gender equality in sports, particularly within the Nordic context. The findings reveal distinct patterns in how different groups perceive and respond to the rule changes. Elite competitors and participants from traditional orienteering regions expressed concerns about preserving competitive traditions, while showing support for expanding women's opportunities. The support varied by competition level and geographic location, with recreational participants and those from urban areas showing higher support for format changes. Unexpectedly, older participants demonstrated stronger support for the changes than younger athletes. These results provide insights for sports organizations implementing similar gender equality initiatives, highlighting the importance of considering various stakeholder perspectives while maintaining competitive integrity.